Synthesis, transformation and biological properties of S-derivatives of 4-amino-5-(5-R-pyrazol-3-yl)-1,2,4-triazole-3-thiol - Fedotov, S. O.; Gotsulya, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (Запорізький державний медико-фармацевтичний університет, 2023)
The main goal of the work is to study the potential of 1,2,4-triazole derivatives as a source of new drug candidates with improved safety and efficacy profiles. The research is aimed at the synthesis and characterization of a number of S-derivatives of 4-amino-5-(5-R-pyrazol-3-yl)-1,2,4- triazol-3-thiol, as well as at the evaluation of their physicochemical properties and biological functions.
Keywords: тези доповідей